2012
DOI: 10.1111/j.1540-8175.2012.01792.x
|View full text |Cite
|
Sign up to set email alerts
|

Parachute Tricuspid Valve in a Patient with Atrial Septal Defect Detected by Two‐ and Three‐Dimensional Echocardiography

Abstract: Atrioventricular valve parachute deformity was generally seen in the mitral position, which is called parachute mitral valve. Parachute deformity is also seen in the tricuspid position, but this has rarely been reported as sporadic cases. All of these cases were associated with other congenital defects, such as double outlet right ventricle, left to right shunt. We herein present two- and three-dimensional echocardiographic features of a parachute tricuspid valve in a patient with atrial septal defect and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Actually a systolic murmur was audible in all 11 patients. In 10 patients, the murmur was audible along the sternal border, and in 1 patient, it was heard in the left intercostal space [ 8 ]. In one of the patients, an additional diastolic murmur was heard at the apex [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually a systolic murmur was audible in all 11 patients. In 10 patients, the murmur was audible along the sternal border, and in 1 patient, it was heard in the left intercostal space [ 8 ]. In one of the patients, an additional diastolic murmur was heard at the apex [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The electrocardiographical results were described for 7 patients: 2 (28.6%) patients had a normal sinus rhythm [ 5 , 7 ], and 5 (71.4%) patients had an abnormal electrocardiogram including right bundle branch block ( n = 1) [ 8 ], conduction defects ( n = 1) [ 6 ], left ventricular hypertrophy ( n = 1) [ 9 ], ST-T changes ( n = 1) [ 5 ], and north-west axis (+ 150°), right atrial enlargement and prominent R wave in the V 1 lead ( n = 1) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly after its description involving the mitral tensor apparatus, it was observed that often, the anomaly was associated with left-sided obstructive lesions and the syndrome was called the Shone complex. 4 Parachute tricuspid valve is a late discovery 5 with a single case each reported with tetralogy of Fallot, 6 double-outlet right ventricle, 7 two cases with atrial septal defect 8,9 and three in isolation. [10][11][12] Most of these cases were not symptomatic due to parachute tricuspid valve.…”
Section: Discussionmentioning
confidence: 99%